The association of dietary fatty acids intake with overall and cause-specific mortality: a prospective cohort study from 1999–2018 cycles of the NHANES - Zhang, Zhaoxiang; Ding, Lei; Liang, Yali; Yang, Hu; Zhu, Yu (Frontiers in Nutrition, 2025)
BackgroundExisting studies have evaluated the association of dietary fatty acids with mortality. However, the findings remained contentious. Our aimed to investigate the association of total dietary fat and each type of fatty acids with overall and cause-specific mortality.MethodsWe conducted a population-based prospective cohort study derived from the U.S. NHANES from 1999 to 2018. Baseline dietary information was assessed utilizing two 24-h dietary recalls. The death status was followed up to December 31, 2019. Hazard ratio (HR) was calculated by Cox regression and competing risk model. The effects of isocaloric replacement saturated fatty acids (SFAs) with monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs) were estimated using the leave-one-out method.ResultsA total of 49,884 U.S. adults were included. 7,347 deaths, including 2,288 and 1,652 deaths from cardio-cerebrovascular disease (CCVD) and cancer, arose during 494,277 person-years. The intake of SFAs was positively associated with an increased risk of overall mortality, with extreme-quintile HR of 1.10 (95% CI: 1.02–1.19, Ptrend = 0.013); whereas an inverse association of PUFAs intake with overall mortality was observed, with extreme-quintile HR of 0.87 (95% CI: 0.81–0.94, Ptrend = 0.001). Greater intake of PUFAs was associated with a lower risk of CCVD-and cancer-specific mortality at borderline statistical significance. The isocaloric substitutions of 5% energy from MUFAs and PUFAs for SFAs was associated with 13 and 12% lower risk of overall mortality.ConclusionGreater intake of SFAs was positively associated with mortality, while greater intake of PUFAs was negatively associated with mortality. Reducing SFA by increasing MUFAs and PUFAs was an attractive strategy to lower mortality.